EXPERIMENTAL TEST OF EFFICIENCY OF TECHNOLOGY OF TRAINING AND PROBLEM SOLVING IN MEDICAL AND BIOLOGICAL PHYSICS - Novikova Iryna Mykolaevna (International Journal of Innovative Technologies in Social Science, 2021)
The article presents the results of research on the introduction of the technological model of professionally oriented tasks in medical and biological physics in the educational process of higher medical institutions (2015 – 2020).The effectiveness of the developed technology for solving professionally oriented problems and tasks, which are based on the method of scientific knowledge, was tested by empirical (assessment of academic achievement, questionnaires, surveys, observations and more) and theoretical (induction, deduction, systems approach, modelling and more) methods of research. The effectiveness of the technological model in the educational process was confirmed by the educational research and the elements of scientific research of students. During the pedagogical experiment were detected problems and contradictions in the process of professional training of future doctors, were described criteria for assessing the academic achievements of students in the discipline of medical and biological physics, including problem solving. The observational experiment showed the insufficiency of the level of formation of natural science and professional competence of students. Control and formative stage of the experiment to assess the effectiveness of the proposed technological content-structural model of solving problems in medical and biological physics, showed the effectiveness of the impact of technology of solving problems in medical and biological physics on the level of positive motivation, level of knowledge, level of educational research and scientific research of students.During the search experiment, technology of solving the tasks, which was confirmed by updated educational and methodical support, was developed. An expert assessment of the effectiveness of the educational process, solving tasks of different levels, levels of skills, and expediency of introduction of educational and methodical support was conducted. The analysis of the results of pedagogical experiment showed the expediency of introduction of developed technology of solving the tasks and training methodical model of support in the educational process. By means of experiment was proved the effectiveness and efficiency of the model of training a specialist in the medical field, in which the leading role belongs to the technological approach to the formation of professional competencies by means of tasks in medical physics, aimed at implementing educational and research activities of students.